Lactic Acid Bacteria in Wine: Technological Advances and Evaluation of Their Functional Role - Virdis, Carla; Sumby, Krista; Bartowsky, Eveline; Jiranek, Vladimir (Frontiers in Microbiology, 2021)
Currently, the main role of Lactic Acid Bacteria (LAB) in wine is to conduct the malolactic fermentation (MLF). This process can increase palatability, improve microbial stability and reduce the acidity of wine. A growing number of studies support the appreciation that LAB can also significantly contribute to the sensorial profile of wine through many different enzymatic pathways. For example, some LAB can enzymatically liberate volatile aromatic compounds, such as glycoside-bound primary aromas, which are odourless in their bound form. LAB can also produce enzymes with the potential to help in the winemaking process and contribute to stabilising the final product. Other reported activities of LAB include: the potential to break down anthocyanin glucosides and impact wine colour, the ability to liberate hydroxycinnamic acids from their tartaric esters, the ability to produce volatile thiols, esterase activity and more. Considering all these findings, this review summarises the novel enzymatic activities of LAB that positively or negatively affect the quality of wine. LAB improvement strategies, their potential to be used as targeted additions, and technological advances involving their use in wine are highlighted along with suggestions for future research.